Entrepreneurial Intention Mahasiswa: Entrepreneurship Education, Entrepreneurial Motivation dan Self-Efficacy - Farida, Eka; Lestari, Purwaningrum Puji; Kholidah, Neneng Rika Jazilatul (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Low entrepreneurial intentions are a serious problem for various parties, including the government, education, industry, and society. Factors that can influence and increase entrepreneurial intentions include entrepreneurship education, motivation and self-efficacy. This study aims to foster entrepreneurial intentions through entrepreneurship education, motivation and self- efficacy. The research approach uses quantitative with explanatory research type. The population was taken from active students and had taken entrepreneurship learning as many as 1392. The sampling technique used the Slovin formula with a sample size of 100 respondents. The data collection technique used a questionnaire, then analyzed using multiple linear regression analysis. The results of the study showed that entrepreneurship education, motivation and self-efficacy had a significant effect on entrepreneurial intentions partially and simultaneously. An important role in improving education through entrepreneurship learning can be one of the potentials to develop and increase self-efficacy in entrepreneurship. In addition, the motivation possessed by students will increase a person's intention to become an entrepreneur.